Environmental assessment of small rivers in the Kiev region (Ukraine) according to the health and hygienic indicators - Shumigay, I.; Tohachynska, O.; Nychyk, O.; Ivanenko, O.; Salavor, O.; Strizhnova, M. (Journal of Plant Stress Physiology, 2015)
The study of water in reservoirs of Ukraine through passive monitoring methods permit to detect heavy metals in the proportion that far exceeds the maximum allowable concentrations. The aim of our article is to analyze the state of aquatic ecosystems of the small rivers of Kiev region according to the toxicological indices. The objects of our research are the superficial waters of the small rivers of Kiev region. Materials and research methods. The ecological assessment of the mentioned was conducted in the different seasons on the basis of analytical research program according to the sanitary indicators. Our researches were made in the Institute of agro-ecology and environmental usage of the national academy of agrarian sciences of Ukraine during 2007-2010. The heavy metals’ content in the water was determined by the extraction of 1 N acid HNO3, and its quantity in the solutions-extracts was found by the atomic adsorption spectrometry. There was analyzed the state of aquatic ecosystems and there was made their ecological assessment based on sanitary indicators. This article presents the results of monitoring of some toxic substances in several small rivers in Kiev region considering the influence of anthropogenic factors. In conclusion nowadays we can provide the ecological safety using waste-free technologies with full utilization of all the raw materials’ constituents. In our future research area we plan to elaborate the ecological control methods of the quality of superficial waters for the small rivers of Kiev.